Pengolahan konten repositori di pusat perpustakaan UIN Syarif Hidayatullah Jakarta - Ulpah Andayani (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2015)
As institutional repositories are part of library materials, it is important to organize these materials properly. An effective organization of library materials is if these materials can be retrieved easily and quickly. This study is aimed to investigate the technical problems regarding with organization of institutional repositories materials such as determining heading, subject access, data accuracy, and other technical problems. By using content analysis, some errors in organizing repositories materials are identified, and then classified into categories. Based on the study, it was found that there are some errors in determining headings, keywords, typeing errors, uploading files, and data entry.